2018
DOI: 10.1002/chir.23037
|View full text |Cite
|
Sign up to set email alerts
|

Separation of eight bedaquiline analogue diastereomers by HPLC on an immobilized polysaccharide‐based chiral stationary phase

Abstract: The high‐performance liquid chromatography (HPLC) is a powerful method in the area of stereoisomer separation. In this study, separation of eight bedaquiline analogue diastereomers (compounds 1‐8) was first examined on a cellulose tris‐(3,5‐dichlorophenylcarbamate) chiral stationary phase, ie, Chiralpak IC in the normal phase mode. The influences of organic modifier types, alcohol content, and column temperature on diastereoseparation were evaluated. Under the optimum chromatographic conditions, all the analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The recovery, precision and the analysis time were similar for both methods, but limit of detection and limit of quantitation as well as linearity range were much better with the HPLC–MS/MS method [ 21 , 42 ]. A Chiralpak IC column was also used for the separation of eight bedaquiline analogue diastereomers [ 43 ]. The retention behavior of several local anesthetics was investigated on five different cellulose-based columns, namely: Lux Cellulose-1 (cellulose tris(3,5-dimethylphenylcarbamate)), Lux Cellulose-2 (cellulose tris(3-chloro-4-methylphenylcarbamate)), Lux Cellulose-3, Lux Cellulose-4 (cellulose tris(4-chloro-3-methylphenylcarbamate)), Lux i-Cellulose-5 (immobilized cellulose tris(3,5-dichlorophenylcarbamate)), and on three amylose-based columns, namely Lux Amylose-1 (amylose tris(3,5-dimethylphenylcarbamate)), Lux Amylose-2 (amylose tris(5-chloro-2-methylphenylcarbamate)), and Lux i-Amylose-3 (immobilized amylose tris(3-chloro-5-methylphenylcarbamate)).…”
Section: Polysaccharide-based Stationary Phasesmentioning
confidence: 99%
“…The recovery, precision and the analysis time were similar for both methods, but limit of detection and limit of quantitation as well as linearity range were much better with the HPLC–MS/MS method [ 21 , 42 ]. A Chiralpak IC column was also used for the separation of eight bedaquiline analogue diastereomers [ 43 ]. The retention behavior of several local anesthetics was investigated on five different cellulose-based columns, namely: Lux Cellulose-1 (cellulose tris(3,5-dimethylphenylcarbamate)), Lux Cellulose-2 (cellulose tris(3-chloro-4-methylphenylcarbamate)), Lux Cellulose-3, Lux Cellulose-4 (cellulose tris(4-chloro-3-methylphenylcarbamate)), Lux i-Cellulose-5 (immobilized cellulose tris(3,5-dichlorophenylcarbamate)), and on three amylose-based columns, namely Lux Amylose-1 (amylose tris(3,5-dimethylphenylcarbamate)), Lux Amylose-2 (amylose tris(5-chloro-2-methylphenylcarbamate)), and Lux i-Amylose-3 (immobilized amylose tris(3-chloro-5-methylphenylcarbamate)).…”
Section: Polysaccharide-based Stationary Phasesmentioning
confidence: 99%
“…The success of improving the synthetic scheme for ( S )‐ 1 (Figure 2b) prompted us to apply the enantioselective HPLC separation 18,19,26–29 to the synthesis of (1 S ,2 S )‐ 2 (Figure 3B); we expected that the enantioselective HPLC conditions we employed for the separation of ( S )‐ 20 and ( R )‐ 20 would be effective for the diastereoseparation of (1 S ,2 S )‐ 22 and (1 R ,2 S )‐ 22 (step vi), considering their structural analogy. It should also be noted that enantioselective HPLC has often been used for the separation of diastereomers, particularly when physical‐property differences between the diastereomers are small 30,31 . The first half of the new scheme (steps i–iv) was identical to that of the previous one, affording ( S )‐ 21 as the key intermediate.…”
Section: Resultsmentioning
confidence: 96%
“…It should also be noted that enantioselective HPLC has often been used for the separation of diastereomers, particularly when physical-property differences between the diastereomers are small. 30,31 The first half of the new scheme (steps iiv) was identical to that of the previous one, affording (S)-21 as the key intermediate. By using the common NaBH 4 reduction method, the ketone (S)-21 was reduced into a mixture of diastereomeric alcohols (1S,2S)-22 and (1R,2S)-22 in a high yield (85%).…”
Section: Stereocontrolled Synthesis Of (1s2s)-2mentioning
confidence: 88%
“…Literature survey for analytical data of BDQ showed that spectrophotometric method ( 5 ), forced degradation study ( 6 ), simultaneous estimation ( 7 , 8 ), bio-analytical HPLC/MS methods ( 9 , 10 ), chiral analysis ( 11 , 12 ), pharmacokinetic study ( 13 , 14 ) and simultaneous bio-analytical analysis ( 15 ) have been reported till date. The only one reported stability study ( 6 ) does not report the identification of DPs or process related impurities of BDQ.…”
Section: Introductionmentioning
confidence: 99%